Transcriptome Analysis Reveals Key Pathways and Candidate Genes Controlling Seed Development and Size in Ricebean (Vigna umbellata) - Verma, Sachin Kumar; Mittal, Shikha; Gayacharan,; Wankhede, Dhammaprakash Pandhari; Parida, Swarup Kumar; Chattopadhyay, Debasis; Prasad, Geeta; Mishra, Dwijesh Chandra; Joshi, Dinesh Chandra; Singh, Mohar; Singh, Kuldeep; Singh, Amit Kumar (Frontiers in Genetics, 2022)
Ricebean (Vigna umbellata) is a lesser known pulse with well-recognized potential. Recently, it has emerged as a legume with endowed nutritional potential because of high concentration of quality protein and other vital nutrients in its seeds. However, the genes and pathways involved in regulating seed development and size are not understood in this crop. In our study, we analyzed transcriptome of two genotypes with contrasting grain size (IC426787: large seeded and IC552985: small seeded) at two different time points i.e., 5 and 10 days after post-anthesis (DPA). The bold seeded genotype across the time points (B5_B10) revealed 6928 differentially expressed genes (DEGs) whereas, small seeded genotype across the time point (S5_S10) contributed to 14544 DEGs. We have also identified several candidate genes for pod development related traits like seed size, 100-seed weight etc. On the basis of similarity search and domain analysis eight candidate genes (PHO1, cytokinin dehydrogenase, A-type cytokinin, and ARR response negative regulator) related to 100-seed weight and seed size showed down-regulation in small seeded genotype. We have also identified 17497 SSRs for both the genotypes. The MapMan and KEGG analysis confirmed that auxin and cytokinin pathways varied in both the contrasting genotypes and can therefore be the regulators of seed/pod size as well as other pod development related traits in ricebean. A total of 51 genes encoding SCFTIR1/AFB, Aux/IAA, ARFs, E3 ubiquitin transferase enzyme, 26S proteasome showing distinct expression dynamics in bold and small genotypes were also identified. To the best of our knowledge, this is the first transcriptomic study conducted in this crop to understand molecular basis of any trait. It would provide us a comprehensive understanding of the complex transcriptome dynamics during seed development and gene regulatory mechanism of seed size determination in ricebean.